Multivessel revascularization for acute myocardial infarction and cardiogenic shock: when less is more - Abuzaid, Ahmed; Elgendy, Islam Y. (Journal of Emergency and Critical Care Medicine; Vol 2 (February 2018): Journal of Emergency and Critical Care Medicine, 2018)
Cardiogenic shock represents the most dreadful and the primary cause of in-hospital mortality in patients with acute myocardial infarction (AMI) (1). Cardiogenic shock (~80% of cases) occurs due to large infarction, pumps failure, infarct extension, re-infarction, or smaller infarction in preexisting left ventricular dysfunction with or without mechanical complication (2,3). Approximately 5–15% of patients with AMI are in cardiogenic shock at the time of presentation (4). Over the past 3 decades, the incidence of cardiogenic shock has been declining, a finding which has been attributed to widespread adoption of early revascularization and improvement in preventive measures.